Value-Based Administrative Management: Pillars of Sustainability and Quality of Learning at Tahfiz Foundation - Adiyono (ADARA, 2025)
The Qur'anic educational institution is an institution that focuses on learning the Qur'an, and behind the development of an institution there is a strategy that has been well designed and structured. This study aims to investigate the administrative management of tahfiz foundations in building the pillars of sustainability. Using a qualitative case study design, this research involved foundation administrators, ustadz, and santri as participants. Data were collected through in-depth interviews, observation, and document analysis. The findings show that: (1) there are several important components in administrative management that support the sustainability of the foundation, including strategic planning, transparent financial management, and human resource development; (2) these components include core values such as efficiency, accountability, and community involvement; (3) through the implementation of these values, the foundation is able to create an environment that supports quality education and harmonious relations with the community. Thus, administrative management contributes significantly to creating the sustainability of the tahfiz foundations studied, which is reflected in the foundations' capacity to face challenges and adapt to the needs of the surrounding community.